1972
DOI: 10.1104/pp.49.3.345
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Conductance of Differentially Salinized Plants

Abstract: Stomatal resistance was measured daily with a stomatal diffusion porometer during a 4-week period in leaves of bean (Phaseolus vulgaris L., var. Bush Blue Lake) and barley (Hordeum vulgare L., var. Liberty) plants having roots equally split between two differentially salinized nutrient solutions. The stomatal conductance (reciprocal of stomatal resistance) of plants with half their roots in saline solutions was intermediate between the stomatal conductances of plants grown in nonsaline solutions and those grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Stomatal characteristics of the salinized seedlings were not measured in the present study. Kirkham et al (1972) recently observed a decrease in the growth of barley and bean plants previously treated with NaCl. They attributed the reduction in growth to increased stomatal resistance which they measured with a stomatal diffusion porometer.…”
Section: Mineral Element Content Of Shootsmentioning
confidence: 96%
“…Stomatal characteristics of the salinized seedlings were not measured in the present study. Kirkham et al (1972) recently observed a decrease in the growth of barley and bean plants previously treated with NaCl. They attributed the reduction in growth to increased stomatal resistance which they measured with a stomatal diffusion porometer.…”
Section: Mineral Element Content Of Shootsmentioning
confidence: 96%
“…Watering one part of the root system of wheat (Lawlor, 1973) and tomato (Tan et al, 1981) resulted in a compensatory increase in water uptake by other parts of the root system so that plant water relations remained relatively unaffected. However, compensation was not seen in beans and barley because plants with half their roots in saline solutions had growth and water relations values intermediate between those of plants grown in non-saline solutions and plants grown in saline solutions (Kirkham et al, 1969(Kirkham et al, , 1972. Only partial compensation occurred in SO seedlings since plants with half their root systems in either NaCl or PEG solutions had shoot and root dry weight and leaf water and osmotic potential values closer to those of the non-stressed control than to those with completely stressed root system (Tables 16,17).…”
Section: Root Growth and Distribution Under Nacl And Peg Stressesmentioning
confidence: 99%